Percutaneous Embolization of Congenital Portosystemic Venous Fistula in an Infant with Down Syndrome. (19th September 2013) - Tanya Chun, Pattaraporn; Chun, Terrence; Files, Matthew; Vo, Nghia; McAdams, Ryan M.
Abstract : Congenital intrahepatic portosystemic venous shunts are rare vascular malformations often associated with severe complications. We describe a term male infant with Down syndrome with high output heart failure secondary to a congenital arterial to portal venous fistula that was diagnosed by Doppler ultrasound. Percutaneous embolizations of the left hepatic vein, portal vein, and communicating fistulas were performed without complications, resulting in clinical improvement. A subsequent hepatic ultrasound demonstrated resolution of the pathologic fistulous communication and shunting effects.